Ossifying fibrous epulis: case reports and diagnostic insights into gingival swellings - Ibrahim, Nurul Ruziantee; Mohd Ali, Mohd Nor Hafizi (IIUM Press, 2026)
Ossifying fibrous epulis, also known as peripheral ossifying fibroma in literature, is a relatively common, benign reactive lesion that exclusively affects the gingival tissue. It arises in response to chronic local irritation such as plaque accumulation, calculus, faulty restorations, or repeated trauma. Though non-neoplastic in nature, it can present as a slowly enlarging, firm, and fibrous mass, mimicking a range of other more aggressive or neoplastic conditions. Histopathological examination is paramount for achieving a definitive diagnosis. This report presents two cases occurring in young adults, highlighting the clinical features, diagnostic process, surgical management, and post-operative outcomes. The lesions, located in the anterior maxilla and mandibular gingiva respectively, shared common clinical traits including nodular appearance, surface colour resembling surrounding mucosa, and occasional bleeding upon provocation. Histopathological analysis in both cases revealed parakeratinised stratified squamous epithelium with focal degeneration, mineralized components such as trabeculae of bone and cementum-like materials, and chronic inflammatory cells infiltrate. Following surgical excision and removal of local irritants, healing was uneventful with no recurrence observed during short-term follow-up. This paper further elaborates on the histopathological spectrum, recurrence risk, and differential diagnosis of ossifying fibrous epulis, supported by a tabulated overview of similar gingival lesions. Recognising the clinical behaviour and key distinguishing features of this lesion is crucial in general dental practice to avoid misdiagnosis and ensure appropriate intervention. Early detection, thorough removal, and patient education are integral to effective management and prevention of recurrence